Visual analysis of research hotspots and trends in traditional Chinese medicine for depression in the 21st century: A bibliometric study based on citespace and VOSviewer - Chengcheng Song; Kelong Chen; Yongxi Jin; Ling Chen; Zuxiu Huang (Heliyon)
Background and objectives: Depression long been a key concern for scholars worldwide; however, the field of depression has not received sufficient attention in traditional Chinese medicine. It was not until the 21st century that research into depression gradually entered a period of rapid development, with an increasing number of academic studies published in major journals. However, one limitation of this field is that no scholars have yet summarised the development process and key research issues. Therefore, the present study aimed to summarise the research trends and progress in this field, providing relevant information and presenting potential future research directions for subsequent researchers. Methods: Literature in this field was searched from January 1, 2000 to April 20, 2024 in the Web of Science Core Collection database, to analyse the current status of the literature and publication trends. Bibliographic information, including study authors, organisations, keywords, countries, references, citations, and co-citations, was extracted using CiteSpace and VOSviewer software for quantitative analysis, visual mapping, and scientific evaluation. Results: A total of 921 papers were included, with a significant increase in the number of publications from 2017 to 2021, and a stable number of more than 140 publications between 2022 and 2023, with publications in these two years accounting for 31.38 % of the total. The Journal of Ethnopharmacology had the highest number of publications (97) and citations (2067), as well as the highest number of co-citations (1369). China (847 publications, 13256 citations), Beijing University of Chinese Medicine (90 publications, 1232 citations), and Qin Xuemei (30 publications, 759 citations) were the most prolific and influential countries, organisations, and authors in the field, respectively. Keyword clustering co-occurrence analysis revealed nine different clusters with good homogeneity. The top three clusters were randomised controlled trials, traditional Chinese medicine, and hippocampal neurogenesis. In the timeline analysis of keywords, from 2000 to 2010, keywords in this field were concentrated on hippocampal neurology and forced swimming test as clustering axes of Traditional Chinese Medicine. From 2010 to 2020, the research hotspots focused on randomised controlled trials and hippocampal neurogenesis. After 2020, keywords became more focused on network pharmacology. In addition, the occurrence time of explosive keywords were distributed before 2010 and after 2020. Before 2010, these keywords included the forced swimming test, Tail Suspension Test, Chronic Cold Stress, Neural Regeneration, and Banxia Houpu Decoction. Conversely, network Pparmacology and Molecular Docking arose as key buzzwords starting in 2020. Conclusions: This study comprehensively analysed and summarised the research hotspots and trends in this field of research in the 21st century from a bibliometric perspective, further generating a series of visual graphs to help researchers understand the current research status, potential collaborators, collaborating institutions, and potential future research hotspots in this field.